Contribuciones al problema de la unidad del Himno homérico a Apolo (Argos, 2025)
The problem of the unity of the Homeric hymn to Apollo has a long tradition in modern philology, since in 1782 Ruhnken posited that the text that we have is actually constituted of two distinct hymns. I intend, firstly, to systematize briefly the different arguments, both the current and the traditional ones, in favor and against this idea, with their correspondent counter-arguments, and then to link this debate to a wider approximation to ancient hymnody that, perhaps without adding new proofs for Ruhnken’s tesis, might provide a new perspective for it, which, I hope, contributes to the problem.
Keywords: Homer; Homeric hymns; Apollo; unity; Greek hymnody